Human mastadenovirus pneumonia in two immunocompetent patients - Salome Hosch; Baptiste Hamelin; Jasmin D. Haslbauer; Christopher M. Field; Albert Heim; Lucas Boeck; Spasenija Savic Prince; Tanja A. Gradistanac; Anita E. Gander; Peter M. Keller; Karoline Leuzinger; Kirsten D. Mertz (Virology Journal)
Abstract Background Human adenoviruses (hAdV) are common pathogens associated with acute respiratory tract infections. Mastadenovirus blackbeardi (hAdV-B) has been linked to severe pneumonia and disseminated disease, primarily in immunocompromised patients. The histopathological and clinical features of adenoviral pneumonia remain poorly characterized. Case presentation We report two cases of hAdV-B pneumonia in immunocompetent female patients with a history of smoking. Both patients are of Caucasian origin and reside in Switzerland. They presented with persistent respiratory symptoms, pulmonary infiltrates on CT scans, and necrotizing granulomatous inflammation in lung tissue. After excluding other pathogens, metagenomic whole-genome sequencing identified hAdV-B in both cases. Both patients recovered fully following wedge resection of the affected lung tissue, without the need for additional therapy. Conclusions These two cases demonstrated a remarkably similar clinical and histopathological profile, characterized by chronic granulomatous lung inflammation. The findings suggest a prolonged inflammatory response leading to persistent tissue damage. Our observations highlight the potential of hAdV-B to cause chronic pneumonia even in otherwise healthy individuals.